The Research Institute for Sport and Exercise Sciences (RISES) at Liverpool John Moores University (2009)
Homepage of Research Instituts of Sport and Exercise at Liverpools John Moores University. (Main areas: chronobiology and exercise, exercise and health, sport and exercise performance). Mission statement: RISES will deliver cutting edge research and high quality research training, delivered by world class staff in state-of-the-art facilities. The Research Institute for Sport and Exercise Sciences (RISES) was established in 1997 and continues to be the cutting-edge and vibrant home of research activity within the School of Sport and Exercise Sciences. The success of RISES staff since its inception in 1997 is obvious and a high profile international reputation has been gained for its Research Training and Research Outputs. Across broad but multi-disciplinary research areas the RAE in 2001 rated the Institute as 5**. In the most recent RAE 2008 RISES submitted 22 staff and maintained its position as a leading research centre in the UK with recognition of its world leading and world-class activities. The focus of RISES is to provide structures, support, critical mass and a focus for all of the research work being undertaken and to provide a clear link to teaching and enterprise. In this way world leading research clearly informs and infuses the curriculum and underpins applied work. The Research Groups and the RISES Advisory Board provide the focus for strategic discussion, policy implementation, staff development of individuals and a focus for evaluation. RISES provides a focus for research activities in the subject area, ranging from studies at cellular level to whole-body responses to exercise and from elite athletes to novices at physical activity. Members of RISES include all staff and research students from within the School, honorary members from external institutions who are collaborators, visiting Honorary Professors and visiting Research Associates. The research projects are funded by grants from charities, industrial sponsors, international agencies, governments and sports bodies. A thriving post-graduate research community provides a cosmopolitan culture and an environment in which international students may flourish.